A two-level coordinated voltage control scheme of electric vehicle chargers in low-voltage distribution networks - Wang, Yu (2020)
Nowadays, a growing number of plug-in electric vehicles are charged by electric vehicle chargers (EVCs) in low-voltage (LV) residential networks. Without proper control, the increasing charge demand together with high PV penetration will lead to severe voltage issues. In this paper, a two-level coordinated voltage control scheme of EVCs is proposed for voltage regulation in LV distribution networks. The proposed control scheme includes two coordinated levels to effectively utilize EVCs. In the higher level, the distributed voltage control based on consensus algorithm achieves equal utilization among EVCs for network voltage regulation. In the lower level, the localized power allocator determines the real and reactive power outputs, considering the power limits and charging requirements of each EVC. The entire control scheme ensures that the voltages along the distribution network are within the allowable voltage ranges while avoid affecting the users’ charging demand. The proposed control method is evaluated in a LV residential distribution network under various operation conditions. The simulation results validate the effectiveness of the proposed method.